P2 / O3 double-phase composite sodium ion battery positive electrode material as well as preparation method and application thereof

By covering the P2 phase layered material on the O3 phase matrix of the positive electrode material of the sodium ion battery, the problem of insufficient stability and electrochemical performance of the sodium ion battery material is solved, high capacity, good cycle performance and simplified preparation process are achieved, suitable for in large-scale energy storage equipment.

CN119297269AActive Publication Date: 2025-01-10HENAN KELONG NEW ENERGY CO LTD

Patent Information

Application Number
CN202411820536.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-01-10
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

The existing sodium ion battery cathode materials have shortcomings in terms of stability and electrochemical performance, especially the problems of structural instability and poor electrochemical performance caused by the differences in the O3 phase and P2 phase materials.

Method used

Using P2/O3 biphase composite sodium ion battery positive electrode material, the P2 phase layered material is coated on the O3 phase matrix to ensure that the transition metal elements are the same and the proportions are close, and the formed cladding layer and matrix structure change smoothly, which enhances the Diffusion properties of sodium ions and material stability.

Benefits of technology

It improves the capacity, recycling performance and rate performance of sodium ion batteries, simplifies the preparation process, enhances the comprehensive performance and application potential of the materials, and is suitable for large-scale energy storage equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297269A_ABST
    Figure CN119297269A_ABST
Patent Text Reader

Abstract

The invention discloses a P2 / O3 double-phase composite sodium ion battery positive electrode material and a preparation method and application thereof.The positive electrode material comprises a base body and a coating layer coating the outer layer of the base body, the base body is composed of an O3-phase material, the space group of the O3-phase material is R-3m, the coating layer is composed of a P2-phase layered material, the space group of the P2-phase layered material is P63 / mmc, chemical elements contained in a P2 phase and chemical elements contained in an O3 phase are the same, and the chemical elements contained in the P2 phase and the chemical elements contained in the O3 phase are the same. The element proportions are relatively close. The sodium-ion battery positive electrode material prepared by the method is relatively high in capacity, excellent in recycling performance and relatively good in rate capability, meanwhile, the preparation method is simple, and the comprehensive performance and the application potential of the positive electrode material are improved. The sodium ion secondary battery prepared on the basis of the positive electrode material is relatively high in first-cycle efficiency, excellent in recycling performance, excellent in rate capability and relatively good in safety performance, and can be used for large-scale energy storage equipment of solar power generation, wind power generation, intelligent power grid peak regulation, distributed power stations, backup power supplies or communication base stations.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of P2 / O3 dual-phase composite sodium ion battery positive electrode materials, and specifically relates to a P2 / O3 dual-phase composite sodium ion battery positive electrode material and a preparation method and application thereof. Background Art

[0002] The development of industry and the consumption of fossil fuels have led to an energy crisis, which ultimately drives the demand for efficient energy storage devices. The consumption of fossil fuels releases greenhouse gases such as carbon dioxide, which leads to climate change, desertification, and global warming. In addition, fossil fuel resources (coal, oil, and natural gas) are gradually decreasing. Therefore, it is imperative to develop environmentally friendly and sustainable energy storage devices using clean or renewable energy sources such as solar, hydro, and wind power, as these resources are cost-effective and sustainable. These energy sources also depend on environmental conditions such as temperature, location, and season. Therefore, it is necessary to integrate energy storage devices with superior stability and capacity. Therefore, rechargeable / secondary batteries will play a key role in optimal energy storage devices due to their flexible response time, high energy density, long life cycle, pollution-free operation, high efficiency, and portability. Lithium-ion batteries (LIBs) have become an essential component of electronic and portable devices (laptops, mobile phones, tablets, cameras, etc.) due to their excellent energy density (Ed), power density (Pd), efficiency, stable capacity, low self-discharge, light weight, and long life. However, lithium resources are unevenly distributed and have limited reserves. In addition, as consumption increases, the cost of lithium gradually increases. Therefore, large-scale energy storage of lithium-ion batteries will inevitably be limited.

[0003] Therefore, in the field of energy storage, it is necessary to find a secondary battery system that can supplement or even replace lithium-ion batteries. Since sodium ions and lithium ions are in the same main group, their chemical properties are similar, and sodium is abundant and evenly distributed on the earth, and its cost is low, the development of sodium-ion secondary batteries as large-scale energy storage devices is an alternative option.

[0004] Patent document CN116314659A discloses a layered oxide with a mixed phase structure and its preparation method and application. By coating a layer of P2 phase material on the surface of O3 phase material, the coating structure combines the high-capacity core O3 phase and the structurally stable shell P2 phase, thereby improving the reversibility and air stability of the positive electrode material, reducing the surface residual alkali and improving the rate performance. However, in the patent technology, the O3 phase material contains Fe element, while the P2 phase material does not contain Fe element. The elements of the O3 phase material and the P2 phase material are quite different, which will affect the stability and electrochemical performance of the positive electrode material to a certain extent.

[0005] The patent document of CN117976884A discloses a core-shell structure sodium ion battery positive electrode material and its preparation method and application. The core-shell structure sodium ion battery positive electrode material includes a core, an outer shell and a transition layer between the core and the outer shell; the core includes an O3 phase positive electrode material, the outer shell includes a P2 phase positive electrode material, and the transition layer includes a P2-O3 mixed phase positive electrode material. The core-shell structure sodium ion battery positive electrode material adopts an O3 phase material as the core, and then sequentially coats the P2-O3 mixed phase positive electrode material and the P2 phase material. Through the transition of the P2-O3 mixed phase coating layer, the material not only has the advantages of the P2 phase and the O3 phase material, but also can prevent the coating layer from falling off and the positive electrode material from cracking due to the inconsistent lattice expansion coefficients of the P2 and O3 phases during the material charging and discharging process. However, the core-shell structure sodium ion battery positive electrode material in this patented technology contains a P2-O3 mixed phase positive electrode material transition layer, which makes the preparation process relatively complicated. Summary of the invention

[0006] The technical problem solved by the present invention is to provide a P2 / O3 two-phase composite sodium ion battery positive electrode material and a preparation method thereof. The sodium ion battery positive electrode material prepared by the method has high capacity, excellent cycle performance, and good rate performance. At the same time, the preparation method is simple, which improves the comprehensive performance and application potential of the positive electrode material. The sodium ion secondary battery prepared based on the positive electrode material has high first-week efficiency, excellent cycle performance, excellent rate performance and good safety performance, and can be used for large-scale energy storage equipment such as solar power generation, wind power generation, smart grid peak regulation, distributed power stations, backup power supplies or communication base stations.

[0007] The present invention adopts the following technical solution to solve the above technical problems: a P2 / O3 two-phase composite sodium ion battery positive electrode material, the positive electrode material comprising a substrate and a coating layer coated on the outer layer of the substrate; The matrix is ​​composed of O3 phase Na 1+a Ni x Mn y M1 z M2 b O 2 The material composition has a space group of R-3m, wherein M1 is a transition metal element, specifically one or more of Ti, Fe, Co, Cu or Zn, M2 is a doping element, specifically one or more of Mg, Zr, Nb, Mo, Sn, Sb, Be, Ta, B, W, Y or Cr, -0.05≤a≤0.05, 0.1≤x≤0.5, 0.1≤y≤0.5, 0.05≤z≤0.4, 0≤b≤0.01, x+y+z=1; The coating layer is composed of P2 phase Na c Ni d Mn e M1 f O2 It is composed of layered materials with a space group of P63 / mmc, wherein the transition metal element M1 in the P2 phase layered material is the same as the transition metal element M1 in the matrix, 0.5≤c≤0.7, d=x±0.2, e=y±0.2, f=z±0.2.

[0008] Preferably, the molar percentage of the coating layer in the sodium ion battery positive electrode material is 0.1% to 50%.

[0009] Preferably, the molar percentage of the coating layer in the sodium ion battery positive electrode material is 1% to 30%.

[0010] The transition metal elements contained in the P2 phase and the O3 phase in the sodium ion battery positive electrode material of the present invention are the same, but the element ratios are slightly different. This is because the same elements can grow more closely during the coating process, and the structural changes of the contact surface between the P2 phase and the O3 phase are relatively stable, which can reduce the contact surface to Na + The impact of transmission on the electrochemical performance of sodium-ion batteries can be effectively guaranteed.

[0011] The preparation method of the P2 / O3 dual-phase composite sodium ion battery positive electrode material of the present invention comprises the following specific steps: Step S1: The sodium source, the nickel-manganese precursor, the M1 source, and the M2 source are weighed and mixed evenly according to the required stoichiometric ratio, and heat-treated at 700-1000°C for 10-20h in an air atmosphere to obtain the O3 phase matrix material Na 1+a Ni x Mn y M1 z M2 b O 2 , the sodium source is one or more of sodium carbonate, sodium bicarbonate, sodium sulfate, sodium bisulfate, sodium oxalate, sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium peroxide, sodium hydroxide, sodium nitrate, sodium acetate or sodium superoxide, the nickel manganese precursor is nickel manganese hydroxide or nickel manganese carbonate, the M1 source and the M2 source are one or more of the oxides, hydroxides, carbonates, chlorides, nitrates, acetates or sulfates corresponding to M1 and M2, respectively, M1 is a transition metal element, specifically one or more of Ti, Fe, Co, Cu or Zn, and M2 is a doping element, specifically one or more of Mg, Al, Zr, Nb, Mo, Sn, Sb, Be, Ta, B, W, Y or Cr; Step S2: The base material obtained in step S1 is mixed evenly with the sodium source, nickel source, manganese source and M1 source corresponding to the surface coating element, and heat treated at 700-1000°C for 5-15h in an oxygen-containing atmosphere to obtain the coated P2 phase Na c Ni dMn e M1 f O 2 The P2 / O3 two-phase composite sodium ion battery positive electrode material of the layered material, the sodium source is one or more of sodium carbonate, sodium bicarbonate, sodium sulfate, sodium bisulfate, sodium oxalate, sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium peroxide, sodium hydroxide, sodium nitrate, sodium acetate or sodium superoxide, and the nickel source, manganese source and M1 source are one or more of the oxides, hydroxides, carbonates, chlorides, nitrates, acetates or sulfates corresponding to Ni, Mn and M1.

[0012] Preferably, the materials are mixed in steps S1 and S2 by dry mixing, such as ball milling or high mixing, in order to mix the materials uniformly, regardless of the mixing conditions, as long as the materials can be mixed uniformly.

[0013] Preferably, the particle size of the nickel manganese precursor in step S1 is 1-15 μm.

[0014] Preferably, the morphology of the sodium ion battery cathode material in step S2 includes any one of block, lamellar, disc or spherical. The morphology of the sodium ion battery cathode material may vary due to different ratios of Na to metal or different precursors.

[0015] Preferably, the temperature selected for sintering in step S1 is 800-970°C, the sintering time is 13-18h, and the heating rate of the sintering process is 2-10°C / min; the temperature selected for sintering in step S2 is 850-950°C, the sintering time is 8-12h, the heating rate of the sintering process is 2-10°C / min, and the oxygen-containing atmosphere is an oxygen atmosphere or a CO2-free atmosphere. 2 Air atmosphere.

[0016] Preferably, the base material after the primary sintering in step S1 is a single crystal rather than a secondary sphere, and the particle size D50 of the base material is 3-10 μm.

[0017] In the sodium ion battery positive electrode material of the present invention, for the coating layer being a P2 phase, the coating layer and the substrate have the same type of transition metal elements, the sodium ion stoichiometric coefficient ratio of the coating layer and the substrate is maintained between 0.45 and 0.7, and the ratio of the transition metal elements in the coating layer is close to that in the substrate, so as to ensure that the growth of the coating layer on the substrate is more closely fitted.

[0018] The present invention provides a sodium ion secondary battery comprising the positive electrode material.

[0019] The present invention provides a use of the sodium ion secondary battery, wherein the sodium ion secondary battery is used for large-scale energy storage equipment of solar power generation, wind power generation, smart grid peak regulation, distributed power stations, backup power supplies or communication base stations.

[0020] Compared with the prior art, the present invention has the following advantages and beneficial effects: 1. The sodium ion battery material prepared by the present invention is composed of an inner O3 phase matrix and an outer P2 phase coating layer, wherein the P2 phase and the O3 phase contain the same chemical elements, and the element ratio is relatively close. The same elements can ensure that the structural changes of the coating layer and the matrix at the contact surface are relatively stable as much as possible, which has a positive effect on Na + The diffusion effect is small, which is beneficial to the Na + diffusion of O3 relative to Na in P2 phase + The supplementation can also reduce the phase transformation of the P2 phase, and can effectively enhance the structural stability, air stability and water stability of the positive electrode material, so that the sodium ion battery prepared based on the positive electrode material has better rate performance and cycle stability.

[0021] 2. The core-shell structure sodium ion battery positive electrode material prepared by the present invention is simple to prepare and has better comprehensive performance and application prospects, including higher capacity, better rate performance and recycling performance, good safety performance, and great practical value. It can be used for large-scale energy storage equipment such as solar power generation, wind power generation, smart grid peak regulation, distributed power stations, backup power supplies or communication base stations. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the SEM image of the positive electrode material prepared in Example 1.

[0023] Figure 2 This is the XRD diagram of the positive electrode material prepared in Example 1.

[0024] Figure 3 The charge and discharge comparison curves of the substrate prepared in Example 1 and the coated positive electrode material are shown in FIG.

[0025] Figure 4 The figure is a comparison curve of the capacity cycle retention rate of button-type half-cells assembled with the positive electrode materials prepared in Examples 1-2 and Comparative Examples 1-2. DETAILED DESCRIPTION

[0026] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples, and all technologies implemented based on the above contents of the present invention belong to the scope of the present invention. Example 1

[0027] In this embodiment, the core of the sodium ion battery positive electrode material is O3 phase NaNi 0.4 Mn 0.4 Ti 0.1 Zn 0.1 Zr0.01 O 2 Material, coating layer is P2 phase Na 0.5 Ni 0.2 Mn 0.6 Ti 0.1 Zn 0.1 O 2 The layered material has a molar ratio of the core to the coating layer of 8:2. The precursor is prepared by a co-precipitation method, and the positive electrode material is prepared by a solid phase method.

[0028] According to the stoichiometric ratio of the above matrix, NiSO 4 、MnSO 4 and NH 3 ·H 2 O was used as raw material to prepare Ni mol :Mn mol = 1, the particle size of the precursor is D50 = 4 μm; the precursor is mixed with Na 2 CO 3 、TiO 2 、ZnO、ZrO 2 After weighing according to the stoichiometric ratio, the mixture was ball-milled at a speed of 150 r / min for 5 h. The mixture was placed in a sagger, and heated to 920°C at a heating rate of 3°C / min in a box-type furnace under air atmosphere, and sintered at this temperature for 14 h. After the reaction was completed, the mixture was cooled to room temperature in the furnace, and crushed and sieved to obtain an O3 phase matrix material, the matrix material grains of which were hexagonal flakes with a particle size of D50=6 μm. The matrix material obtained by the above reaction is mixed with Na 2 CO 3 、NiO、Mn 3 O 4 、TiO 2 And ZnO according to the O3 phase: P2 phase, that is, the chemical formula is NaNi 0.4 Mn 0.4 Ti 0.1 Zn 0.1 Zr 0.01 O 2 :Na 0.5 Ni 0.4 Mn 0.4 Ti 0.1 Zn 0.1 O 2 The mass calculated by the stoichiometric ratio corresponding to the molar ratio of 8:2 was weighed, and then mixed and ball-milled at a speed of 150r / min for 5h. After the materials were mixed evenly, they were placed in a sagger and put into a box furnace to remove CO. 2The material was heated to 900°C at a heating rate of 3°C / min in an air atmosphere, sintered at this temperature for 8 hours, cooled to room temperature with the furnace, and crushed and sieved to obtain a P2 phase-coated O3 phase material, i.e., a P2 / O3 dual-phase composite sodium ion battery positive electrode material. Example 2

[0029] In this embodiment, the core of the sodium ion battery positive electrode material is O3 phase NaNi 0.3 Mn 0.5 Ti 0.1 Zn 0.1 Al 0.005 O 2 Material, coating layer is P2 phase Na 0.6 Ni 0.2 Mn 0.6 Ti 0.1 Zn 0.1 O 2 The layered material has a molar ratio of the core to the coating layer of 9:1. The precursor is prepared by a co-precipitation method, and the positive electrode material is prepared by a solid phase method.

[0030] According to the stoichiometric ratio of the above matrix, NiSO 4 、MnSO 4 and NH 3 ·H 2 O was used as raw material to prepare Ni mol :Mn mol =3:5 precursor, the particle size of the precursor is D50=5μm; the precursor is mixed with Na 2 CO 3 、TiO 2 、ZnO、Al 2 O 3 After weighing according to the stoichiometric ratio, the mixture was ball-milled at a speed of 150 r / min for 5 h. The mixture was placed in a sagger, and heated to 940°C at a heating rate of 3°C / min in a box-type furnace under air atmosphere, and sintered at this temperature for 14 h. After the reaction was completed, the mixture was cooled to room temperature in the furnace, and crushed and sieved to obtain an O3 phase matrix material, the matrix material grains of which were hexagonal flakes with a particle size of D50=6 μm. The matrix material obtained by the above reaction is mixed with Na 2 CO 3 、NiO、Mn 3 O 4 、TiO 2 And ZnO according to the O3 phase: P2 phase, that is, the chemical formula is NaNi 0.3 Mn 0.5 Ti 0.1 Zn 0.1 Al 0.005 O2 :Na 0.6 Ni 0.4 Mn 0.4 Ti 0.1 Zn 0.1 O 2 The mass calculated by the stoichiometric ratio corresponding to the molar ratio of 9:1 was weighed, and then mixed and ball-milled at a speed of 150r / min for 5h. After the materials were mixed evenly, they were placed in a sagger and put into a box furnace to remove CO. 2 The temperature was raised to 920°C at a heating rate of 3°C / min in an air atmosphere, sintered at this temperature for 8 hours, cooled to room temperature with the furnace, and crushed and sieved to obtain a P2 phase-coated O3 phase material, namely a P2 / O3 dual-phase composite sodium ion battery positive electrode material. Example 3

[0031] In this embodiment, the core of the sodium ion battery positive electrode material is O3 phase NaNi 0.3 Mn 0.5 Fe 0.1 Zn 0.1 O 2 Material, coating layer is P2 phase Na 0.6 Ni 0.2 Mn 0.6 Fe 0.1 Zn 0.1 O 2 The layered material has a molar ratio of the core to the coating layer of 9:1. The precursor is prepared by a co-precipitation method, and the positive electrode material is prepared by a solid phase method.

[0032] According to the stoichiometric ratio of the above matrix, NiSO 4 、MnSO 4 and NH 3 ·H 2 O was used as raw material to prepare Ni mol :Mn mol =3:5 precursor, the particle size of the precursor is D50=5μm; the precursor is mixed with Na 2 CO 3 , Fe 2 O 3 , ZnO were weighed according to the stoichiometric ratio and then mixed and ball-milled. The ball-milling speed was 150r / min and the ball-milling time was 5h. The mixture was placed in a sagger and placed in a box furnace and heated to 940°C at a heating rate of 3°C / min in an air atmosphere. The mixture was sintered at this temperature for 14h. After the reaction was completed, the mixture was cooled to room temperature in the furnace. After crushing and sieving, an O3 phase matrix material was obtained. The matrix material had hexagonal flake grains with a particle size of D50=6μm. The matrix material obtained by the above reaction is mixed with Na 2 CO3 、NiO、Mn 3 O 4 , Fe 2 O 3 And ZnO according to the O3 phase: P2 phase, that is, the chemical formula is NaNi 0.3 Mn 0.5 Fe 0.1 Zn 0.1 O 2 :Na 0.6 Ni 0.4 Mn 0.4 Fe 0.1 Zn 0.1 O 2 The mass calculated by the stoichiometric ratio corresponding to the molar ratio of 9:1 was weighed, and then mixed and ball-milled at a speed of 150r / min for 5h. After the materials were mixed evenly, they were placed in a sagger and put into a box furnace to remove CO. 2 The temperature was raised to 920°C at a heating rate of 3°C / min in an air atmosphere, sintered at this temperature for 8 hours, cooled to room temperature with the furnace, and crushed and sieved to obtain a P2 phase-coated O3 phase material, namely a P2 / O3 dual-phase composite sodium ion battery positive electrode material.

[0033] Comparative Example 1 In this comparative example, the core of the sodium ion battery positive electrode material is O3 phase NaNi 0.3 Mn 0.5 Fe 0.1 Cu 0.1 O 2 Material, coating layer is P2 phase Na 0.6 Ni 0.2 Mn 0.6 Ti 0.1 Zn 0.1 O 2 The layered material has a molar ratio of the core to the coating layer of 9:1. The precursor is prepared by a co-precipitation method, and the positive electrode material is prepared by a solid phase method.

[0034] According to the stoichiometric ratio of the above matrix, NiSO 4 、MnSO 4 and NH 3 ·H 2 O was used as raw material to prepare Ni mol :Mn mol =3:5 precursor, the particle size of the precursor is D50=5μm; the precursor is mixed with Na 2 CO 3 , Fe 2 O 3, CuO were weighed according to the stoichiometric ratio and then mixed and ball-milled at a speed of 150 r / min for 5 h. The mixture was placed in a sagger and placed in a box furnace, heated to 960°C at a heating rate of 3°C / min in an air atmosphere, sintered at this temperature for 14 h, cooled to room temperature with the furnace after the reaction was completed, crushed and sieved to obtain an O3 phase matrix material, the matrix material grains were hexagonal flakes, and the particle size D50 = 7 μm; The matrix material obtained by the above reaction is mixed with Na 2 CO 3 、NiO、Mn 3 O 4 、TiO 2 And ZnO according to the O3 phase: P2 phase, that is, the chemical formula is NaNi 0.3 Mn 0.5 Fe 0.1 Cu 0.1 O 2 :Na 0.6 Ni 0.4 Mn 0.4 Ti 0.1 Zn 0.1 O 2 The mass calculated by the stoichiometric ratio corresponding to the molar ratio of 9:1 was weighed, and then mixed and ball-milled at a speed of 150r / min for 5h. After the materials were mixed evenly, they were placed in a sagger and put into a box furnace to remove CO. 2 The temperature was raised to 940°C at a heating rate of 3°C / min in an air atmosphere, sintered at this temperature for 8 hours, cooled to room temperature with the furnace, and crushed and sieved to obtain a P2 phase-coated O3 phase material, namely a P2 / O3 dual-phase composite sodium ion battery positive electrode material.

[0035] Comparative Example 2 In this comparative example, the core of the sodium ion battery positive electrode material is O3 phase NaNi 0.3 Mn 0.5 Ti 0.1 Zn 0.1 Al 0.005 O 2 Material, coating layer is P2 phase Na 0.6 Ni 0.2 Mn 0.6 Fe 0.1 Cu 0.1 O 2 The layered material has a molar ratio of the core to the coating layer of 9:1. The precursor is prepared by a co-precipitation method, and the positive electrode material is prepared by a solid phase method.

[0036] According to the stoichiometric ratio of the above matrix, NiSO 4 、MnSO 4 and NH3 ·H 2 O was used as raw material to prepare Ni mol :Mn mol =3:5 precursor, the particle size of the precursor is D50=5μm; the precursor is mixed with Na 2 CO 3 、TiO 2 、ZnO、Al 2 O 3 After weighing according to the stoichiometric ratio, the mixture was ball-milled at a speed of 150 r / min for 5 h. The mixture was placed in a sagger, and heated to 940°C at a heating rate of 3°C / min in a box-type furnace under air atmosphere, and sintered at this temperature for 14 h. After the reaction was completed, the mixture was cooled to room temperature in the furnace, and crushed and sieved to obtain an O3 phase matrix material, the matrix material grains of which were hexagonal flakes with a particle size of D50=6 μm. The matrix material obtained by the above reaction is mixed with Na 2 CO 3 、NiO、Mn 3 O 4 , Fe 2 O 3 and CuO according to the O3 phase:P2 phase, that is, the chemical formula is NaNi 0.3 Mn 0.5 Ti 0.1 Zn 0.1 Al 0.005 O 2 :Na 0.6 Ni 0.4 Mn 0.4 Fe 0.1 Cu 0.1 The mass calculated by the stoichiometric ratio corresponding to the molar ratio of O2 is 9:1 is weighed, and then mixed and ball-milled. The ball-milling speed is 150r / min and the ball-milling time is 5h. After the materials are mixed evenly, they are placed in a sagger and put into a box furnace to remove CO. 2 The temperature was raised to 920°C at a heating rate of 3°C / min in an air atmosphere, sintered at this temperature for 8 hours, cooled to room temperature with the furnace, and crushed and sieved to obtain a P2 phase-coated O3 phase material, namely a P2 / O3 dual-phase composite sodium ion battery positive electrode material.

[0037] Under the same conditions, the physicochemical indexes and electrical properties of the positive electrode materials obtained in Examples 1 to 3 and Comparative Examples 1 to 2 were evaluated respectively.

[0038] Among them, the residual alkali content test results are shown in Table 1. According to the data, the surface residual alkali of the samples prepared in Examples 1 to 3 is relatively low, which shows that the P2 phase coating method of the same element of the present invention can effectively improve the surface structure and composition of the positive electrode material, which is beneficial to the electrochemical properties of the positive electrode material.

[0039] Table 1 project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 NaOH% 0.0453 0.0823 0.0765 0.1258 0.1433 The SEM image of the positive electrode material prepared in Example 1 is as follows: Figure 1 As shown in the figure, it can be seen that the prepared positive electrode material has a flaky morphology and an average grain size of about 4μm.

[0040] The XRD pattern of the positive electrode material prepared in Example 1 is as follows: Figure 2 As shown, the peaks at 16.3°, 33.1°, 35.5°, 36.8°, 41.7°, 45.1°, 53.3°, 58.0°, 62.9°, and 65.5° represent the O3 phase matrix, and the peaks at 15.8°, 31.7°, 34.3°, 36.1°, 39.2°, 42.8°, and 48.9° represent the peaks of the P2 phase, which indicates that the P2 phase is generated during the coating process.

[0041] The positive electrode materials obtained in Examples 1-2 and Comparative Examples 1-2 were subjected to a button-type half-cell electrical performance test.

[0042] All electrochemical results in Examples 1-2 and Comparative Examples 1-2 were obtained by testing button half-cell CR2032. The main production process includes grinding the positive electrode material, binder polyvinylidene fluoride (PVDF) and conductive agent acetylene black at a mass ratio of 90:5:5, adding an appropriate amount of NMP to obtain a uniform slurry. The slurry is evenly coated on aluminum foil, then dried in an oven at 100°C and punched. Assemble in a vacuum glove box filled with argon, and finally form on a Newway battery test cabinet. Subsequent electrical performance tests were carried out on a Newway battery test cabinet and a ZahnerIM6ex electrochemical workstation.

[0043] Among them, the first charge and discharge curves of the positive electrode material prepared in Example 1 before and after coating are as follows: Figure 3 As shown, after coating, the first charge capacity is reduced compared with the substrate, the discharge specific capacity remains unchanged, and the first efficiency is increased, indicating that the P2 phase after coating does not have a significant effect on the capacity of the positive electrode material.

[0044] The results of the charging cycle test of the positive electrode materials assembled in Examples 1-2 and Comparative Examples 1-2 are as follows: Figure 4As shown in the figure, it can be seen that compared with comparative examples 1~2, embodiments 1~2 have better cycle stability performance. Embodiment 1 can still maintain a capacity retention rate of 93.15% after 100 cycles, and the capacity retention rate of embodiment 2 after 100 cycles is 89.04%, while the capacity retention rate of comparative example 1 after 100 cycles has dropped to 83.31%, and the capacity retention rate of comparative example 2 after 100 cycles has dropped to 84.62%, which indicates that the cycle stability performance of the sodium ion battery positive electrode material prepared by the specific process of the present invention is greatly improved.

[0045] The above embodiments describe the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for illustrating the principles of the present invention. Without departing from the scope of the principles of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of protection of the present invention.

Claims

1. A P2 / O3 dual-phase composite sodium ion battery positive electrode material, characterized in that: The positive electrode material comprises a substrate and a coating layer coated on the outer layer of the substrate; The matrix is ​​composed of O3 phase The material composition has a space group of R-3m, wherein M1 is a transition metal element, specifically one or more of Ti, Fe, Co, Cu or Zn, M2 is a doping element, specifically one or more of Mg, Zr, Nb, Mo, Sn, Sb, Be, Ta, B, W, Y or Cr, -0.05≤a≤0.05, 0.1≤x≤0.5, 0.1≤y≤0.5, 0.05≤z≤0.4, 0≤b≤0.01, x+y+z=1; The coating layer is composed of P2 phase It is composed of layered materials with a space group of P63 / mmc, wherein the transition metal element M1 in the P2 phase layered material is the same as the transition metal element M1 in the matrix, 0.5≤c≤0.7, d=x±0.2, e=y±0.2, f=z±0.

2.

2. The P2 / O3 dual-phase composite sodium ion battery positive electrode material according to claim 1, characterized in that: The molar percentage of the coating layer in the sodium ion battery positive electrode material is 0.1% to 50%.

3. The P2 / O3 dual-phase composite sodium ion battery positive electrode material according to claim 1, characterized in that: The molar percentage of the coating layer in the sodium ion battery positive electrode material is 1% to 30%.

4. A method for preparing the P2 / O3 dual-phase composite sodium ion battery positive electrode material according to claim 1, characterized in that The specific steps are: Step S1: The sodium source, the nickel-manganese precursor, the M1 source, and the M2 source are weighed and mixed evenly according to the required stoichiometric ratio, and heat-treated at 700-1000°C for 10-20h in an air atmosphere to obtain an O3 phase matrix material. , the sodium source is one or more of sodium carbonate, sodium bicarbonate, sodium sulfate, sodium bisulfate, sodium oxalate, sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium peroxide, sodium hydroxide, sodium nitrate, sodium acetate or sodium superoxide, the nickel manganese precursor is nickel manganese hydroxide or nickel manganese carbonate, the M1 source and the M2 source are one or more of the oxides, hydroxides, carbonates, chlorides, nitrates, acetates or sulfates corresponding to M1 and M2, respectively, M1 is a transition metal element, specifically one or more of Ti, Fe, Co, Cu or Zn, and M2 is a doping element, specifically one or more of Mg, Al, Zr, Nb, Mo, Sn, Sb, Be, Ta, B, W, Y or Cr; Step S2: The base material obtained in step S1 is mixed evenly with the sodium source, nickel source, manganese source and M1 source corresponding to the surface coating element, and heat treated at 700-1000°C for 5-15h in an oxygen-containing atmosphere to obtain a coated P2 phase. The P2 / O3 two-phase composite sodium ion battery positive electrode material of the layered material, the sodium source is one or more of sodium carbonate, sodium bicarbonate, sodium sulfate, sodium bisulfate, sodium oxalate, sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium peroxide, sodium hydroxide, sodium nitrate, sodium acetate or sodium superoxide, and the nickel source, manganese source and M1 source are one or more of the oxides, hydroxides, carbonates, chlorides, nitrates, acetates or sulfates corresponding to Ni, Mn and M1.

5. The method for preparing the P2 / O3 dual-phase composite sodium ion battery positive electrode material according to claim 4, characterized in that: The particle size of the nickel manganese precursor in step S1 is 1-15 μm.

6. The method for preparing the P2 / O3 dual-phase composite sodium ion battery positive electrode material according to claim 4, characterized in that: The morphology of the sodium ion battery positive electrode material in step S2 includes any one of block, lamellar, disc or spherical.

7. The method for preparing the P2 / O3 dual-phase composite sodium ion battery positive electrode material according to claim 4, characterized in that: The sintering temperature in step S1 is 800-970°C, the sintering time is 13-18h, and the heating rate of the sintering process is 2-10°C / min; the sintering temperature in step S2 is 850-950°C, the sintering time is 8-12h, the heating rate of the sintering process is 2-10°C / min, and the oxygen-containing atmosphere is an oxygen atmosphere or an air atmosphere excluding CO2.

8. The method for preparing the P2 / O3 dual-phase composite sodium ion battery positive electrode material according to claim 4, characterized in that: The base material after the primary sintering in step S1 is a single crystal, and the particle size D50 of the base material is 3-10 μm.

9. A sodium ion secondary battery, characterized in that: The sodium ion secondary battery comprises the P2 / O3 two-phase composite sodium ion battery positive electrode material as described in any one of claims 1 to 3.

10. Application of the sodium ion secondary battery according to claim 9 in large-scale energy storage equipment for solar power generation, wind power generation, smart grid peak regulation, distributed power stations, backup power supplies or communication base stations.

Citation Information

Patent Citations

  • Core-shell structure sodium ion battery positive electrode material and preparation method and application thereof

    CN117976884A

  • Core-shell structure sodium ion battery positive electrode material and preparation method and application thereof

    CN110277540A

  • Controllable epitaxial sodium ion battery positive electrode material, preparation method thereof and sodium ion battery

    CN114597363A

  • O3 structure layered metal oxide sodium ion battery positive electrode material coated with P2 structure substance and preparation method of O3 structure layered metal oxide sodium ion battery positive electrode material

    CN116435508A

  • Battery positive electrode material and sodium ion battery containing same

    CN117080537A

Cited By

  • P2 / O3 double-phase composite material, preparation method and application thereof, and sodium ion battery

    CN119764431A

  • Sodium-ion battery high-nickel positive electrode material as well as preparation method and application thereof

    CN120072910A